INFLUENCE OF ENTREPRENEURIAL ORIENTATION, MARKET ORIENTATION AND ABSORPTIVE CAPACITY ON BUSINESS PERFORMANCE - Puspitowati, Ida; Royhard, Imanuel Kristoforus (Graduate Program of Universitas Tarumanagara, 2024)
MSMEs became the backbone of the Indonesian economy in 1998 during the crisis, so there is a need for special attention to aspects that can improve the performance of MSMEs. This research was conducted at Pasar Lama Tangerang MSMEs engaged in the food & beverage sector by examining several factors that affect MSME performance, namely entrepreneurial orientation, market orientation and absorptive capacity. In previous studies, there were differences in results from several researchers regarding the determinants of performance, so this study will fill the gap. The theoretical reference used in this study is RBV (Resource Based View) which explains that company success occurs when companies apply the VRIN principle (Valuable, Rare, Inimitable and Nonsubstitable). The brief definition of the four research variables, namely market orientation is the ability of individuals to understand customers and face competitors. Then, entrepreneurial orientation is the ability of individuals to innovate, act proactively and take risks. Furthermore, absorptive capacity is an individual's ability to identify new things and apply them to business. Furthermore, MSME performance is the quality of services provided by businesses to achieve competitive advantage. The purpose of this study was to determine the effect of entrepreneurial orientation, market orientation, and absorptive capacity on the performance of MSMEs. The time horizon used in the study used cross section. The research questionnaire was made with google form and distributed directly to 85 respondents who were culinary MSMEs in the Tangerang Old Market. Sampling was carried out using non-probability sampling techniques with a purposive sampling approach. The data collected will be analyzed using the PLS-SEM method with the SmartPLS 4 software analysis tool. The bootstrapping results of this study indicate that entrepreneurial orientation, market orientation, and absorptive capacity each have a positive and significant effect on MSME performance.